Analysis of the Professional Burnout Syndrome in Times of Pandemic by COVID-19, an Approach to Practice using Artificial Intelligence - Atachagua Galarza, Natalí Ydalia (2023)
In times of pandemic as a result of Covid-19, many of the services provided by the Peruvian state are subject to the parameters of working from home, which is why many of the services are performed in a minimal way, in the case of the syndrome of professional exhaustion, applied to the workers of Line 100, which is dedicated to helping people who are affected by family violence, due to confinement, emergency calls have increased in such a way that workers are subjected to a pressure product of being able to attend to those affected. In this work, the burnout syndrome is analyzed in workers on line 100 for emergency care, which indicates that this syndrome exists in most of the workers, as a result of the same work and the same emotional situation as a result of the Covid- 19, likewise a method is proposed to be able to use Artificial Intelligence in the analysis and prediction of the professional burnout syndrome.